Pergeseran Peran Keluarga Pada Perempuan Migran Sirkuler Dalam Pengembangan Usaha Mandiri Di Sektor Informal - Karningsih Karningsih (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Women as perpetrators of circular mobility (circular migrants) in the city of Semarang are generally involved in independent businesses in the informal sector. Working independently in the informal sector provides economic freedom and power in decision making. The informal sector does not require a lot of skills or working capital, and is suitable for domestic activities. The motivation for circular migrant women to leave their area of origin is because the unfavorable socio-economic conditions in the village encourage village women to engage in independent business in the trade sector, as well as because it is difficult to get work in the village. A shift in family roles occurs in the families of circular migrant women, when women as mothers have to leave the house to earn a living, then childcare patterns are entrusted to parents in the village, even though the existence of circular migrant women remains the hope of all family members, there is a role that is lost in both themselves and family.